PRODUCT DEVELOPMENT IN ISLAMIC BANKS - Adjengdia Bunga Bangsa (Journal of Indonesian Economy and Business (JIEB), 2015)
A book review dealing with Islamic finance mostly on banks. It encompasses the social needs on such product related to the halal priorities.